COMPARATIVE STUDY OF BRAND AWARENESS PLATFORM: FACEBOOK ADS, TIKTOK, GOOGLE DISPLAY NETWORK - Darmawan, Arief Bakhtiar; Dwianto, Rahmad Agus (Widya Komunika, 2024)
This study aims to compare three digital marketing platforms, namely Facebook Ads, Tiktok, and Google Display Network. The three platforms are product marketing media to increase brand awareness. The method used in this research is a literature review from various scientific sources and advertising experience with the three platforms. The aspects compared are strategy, target, cost, and content. This research shows that each platform has advantages depending on the purpose and form of advertising. Facebook Ads are effective for increasing brand awareness according to the adult target market with simple content in the form of images and persuasive text. Facebook advertising costs are low but less effective for advertising in the form of videos. While Tiktok is suitable for enhancing brands with a target market of teenagers, the content needs to be more creative and innovative so that it attracts the attention of the young and teen audience. While the Google Display Network is more effective for enhancing brand awareness with a more mature concept with a broad target market.